(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article presents the results of a comparative study of the continuity of Imam Maturidi’s views on the problem of sensory cognition of the existence of God, the sense of His essence through revelation and reason with religious knowledge of Kazakh thinkers. It is alleged that Imam Maturidi justifies the evidence of the sensory knowledge of man in the knowledge of God. The first Muslim theological scholar, Abu Mansour al-Maturidi, claims that the truth of the universe must be based on knowledge and evidence, not on blind faith. In his book «Kitab at-Tawhid» the evidence of the Creator’s uniqueness is given, and that each thing is dependent on an external factor, and that this is the merit of the Creator. In the path of knowledge of God, Imam Maturidi assigns a huge role to sensory perception and specifically finds сoncrete evidence for this. Unlike modern thinkers, Imam Maturidi seeks to provide a clear proof of human feelings on the path of knowing God. Traditional religious knowledge of Kazakhs places a special place not on external forms, but on the inner content of faith. Since spiritual being can not be known by external senses. Sufficient evidence that the views of the theologian Imam Maturidi are widespread in the Kazakh steppes, especially in the works of songwriters. The world that is felt in the traditional religious knowledge of the Kazakh people is rooted in Kazakh spirituality. That is why the basis of traditional religious beliefs of the Kazakh people is not dominated by material values, but values that are invisible and knowable only through intuition. In general, the article cites the conclusions of Imam Maturidi in the transmission and analysis of spiritual problems of the inner man. Hence the main purpose of writing his book is to demonstrate the infinite wisdom of God. He reveals and proves the nature of divine wisdom, while doing an analysis of the problems related to the creation of the universe, the uniqueness and attributes of God. Key words: Imam Maturidi, sensual cognition, cognizable and unknowable being, religious knowledgeof Kazakhs, unity and being of God.